Proceedings of the First Padang International Conference on Economics Education, Economics, Business and Management, Accounting 2018
DOI: 10.2991/piceeba-18.2018.72
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptance and Use of E-Learning System Among Accounting Lecturers in State and Private Universities in Padang: An Empirical Study Based on UTAUT Model

Abstract: One of the investments of state and private universities to improve the quality of teaching and learning between students and lecturers is the procurement of e-learning system. Due to the large funds of e-learning system investment, the state and private universities need to periodically evaluate whether the lecturers and students have optimally utilized the system. This study aims to find empirical evidence that Unified Acceptance and Use of Technology (UTAUT) model is a conceptual framework to explain the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 7 publications
(13 reference statements)
0
2
0
6
Order By: Relevance
“…Published studies have confirmed the effectiveness of the UTAUT model in investigating the students' acceptance of e-learning. For example, the acceptance and preparedness of students for e-learning in northeastern Thailand [31], a study of e-learning acceptance in postgraduate program at Universitas Negeri Makassar, Indonesia [32], e-learning acceptance level among accounting lecturers in the universities in Padang, Indonesia [33], factors that influence the intent of teachers in higher education to use e-learning in hybrid environments [34], and the evaluation on WhatsApp as a tool for learning during COVID-19 at a Zimbabwean University [35]. However, few if any studies have considered Malaysian post graduate students' behavioural intention to use online learning during the pandemic.…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%
“…Published studies have confirmed the effectiveness of the UTAUT model in investigating the students' acceptance of e-learning. For example, the acceptance and preparedness of students for e-learning in northeastern Thailand [31], a study of e-learning acceptance in postgraduate program at Universitas Negeri Makassar, Indonesia [32], e-learning acceptance level among accounting lecturers in the universities in Padang, Indonesia [33], factors that influence the intent of teachers in higher education to use e-learning in hybrid environments [34], and the evaluation on WhatsApp as a tool for learning during COVID-19 at a Zimbabwean University [35]. However, few if any studies have considered Malaysian post graduate students' behavioural intention to use online learning during the pandemic.…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%
“…Temuan yang sama ditemukan dalam penelitian Sedana & Wisnu (2009), Bendi & Sri (2013), Guo et al, (2015), Prasetyo (2017), Dewi & I Ketut (2017), Agustin dan Mulyani (2016), serta Agustin and Mulyani (2018). Hipotesis penelitian ini berdasarkan hubungan antarvariabel dan temuan riset diatas adalah sebagai berikut: H1: Harapan kinerja berpengaruh positif terhadap niat menggunakan Go-Pay…”
Section: Pengaruh Harapan Kinerja Terhadap Niat Menggunakan Go-payunclassified
“…Semakin tinggi harapan usaha (Effort expectancy) maka semakin tinggi pula niat untuk menggunakan sistem tersebut. Penelitian yang dilakukan oleh Sedana & Wisnu (2009), Bendi & Sri (2013), Prasetyo (2017), Rohmadi et al, (2017), Dewi & I Ketut (2017), Sivathanu (2018), Mohamad & Salina (2018), Agustin dan Mulyani (2016), Agustin and Mulyani (2018), Amrullah & Anjar (2018), dan Wang (2018) menyatakan bahwa variabel harapan usaha berpengaruh terhadap niat menggunakan sistem informasi. Hipotesis penelitian ini berdasarkan hubungan antar variabel dan temuan riset adalah sebagai berikut: H2: Harapan usaha berpengaruh positif terhadap niat menggunakan Go-Pay.…”
Section: Pengaruh Harapan Usaha Terhadap Niat Menggunakan Go-payunclassified
See 2 more Smart Citations